De otio 7 - Williams, Gareth D. (Lucius Annaeus Seneca, 2024)
In De otio 7 Seneca draws on the familiar philosophical idea of the three modes of life – centered, respectively, on pleasure, contemplation, and action1 – in order to argue for the Stoic compatibility between the contemplative and active existences. If he can successfully reconcile the contemplative and active modes of life in ch. 7, Seneca will significantly advance his larger argument in De otio for the Stoic’s justified retirement from the active life either at the end of a career of public service or even before that career begins (2.1-2); for if philosophical contemplation counts as a form of “active” service that benefits the community, the retired life of the mind remains actively and socially beneficial at any stage of one’s existence. In sum, the Stoic commitment to the active life does not end with retirement; rather, what changes is the pathway by which that non-negotiable τέλος is reached.